Validity of behavioral and physiologic parameters for acute pain assessment of term newborn infants - Pereira, Andrea Lübe de S Thiago; Guinsburg, Ruth; Almeida, Maria Fernanda Branco de; Monteiro, Ana Cristina; Santos, Amélia Miyashiro Nunes dos; Kopelman, Benjamin Israel (São Paulo Medical Journal, 1999)
CONTEXT: The subjectivity of pain causes enormous difficulties in evaluating neonatal pain with a single, practical and easy-to-apply tool. Pain evaluation in the neonatal period should be performed by valid, safe, useful and feasible methods. OBJECTIVE: To evaluate the validity of the Neonatal Facial Coding System (NFCS), Neonatal Infant Pain Scale (NIPS), heart rate (HR) and O2 saturation (O2 sat) for neonatal pain assessment. DESIGN: Prospective, double-blind randomized trial. SETTING: A secondary level maternity hospital. PARTICIPANTS: 70 healthy neonates requiring bilirubin dosage were randomly assigned to receive a venous puncture (P: n=33, BW 3.2kg, SD 0.6; GA 39wk, SD 1; 59h of life, SD 25) or an alcohol swab friction (F: n=37; BW 3.1kg, SD 0.5; GA 39wk, SD 1; 52h of life, SD 17). INTERVENTION: All measurements were taken prior to (PRE), during (T0), and 1(T1), 3(T3), 5(T5) and 10(T10) minutes after the procedure. MEASUREMENTS: A neonatologist evaluated NFCS, NIPS, HR and O2 sat by pulse oxymetry. RESULTS: Median NFCS and NIPS results at T0, T1 and T3 were higher in P group, compared to F. More P neonates presented NFCS >2 and/or NIPS >3 at T0, T1 and T3. HR was lower in P group at T1. Average O2 sat was above 90% during the whole study period in both groups. CONCLUSION: NFCS and NIPS are suitable instruments for neonatal pain evaluation. Heart rate and O2 saturation can be used only as auxiliary methods.